The Influence of Card Sort Type Active Learning Strategy on Interests and Responses of Elementary School Students - Agnes Eka Novitasari; Vanda Rezania (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the effect of the Card Sort type as the active learning strategy on the interests and responses of class IV students at an elementary school in Wonoayu, Sidoarjo. It was analyzed on the social studies subject matter which aimed to find out how the influence of the Card Sort type active learning strategy on the students’ interests and responses. The population in this study was 20 students, consisting of 8 male students and 12 female students. This study used a saturated sample which was from those samples' population. The research method used quantitative experimental methods and data processing used the SPSS program. Based on the results of the research and discussion, it can be concluded that the application of the Card Sort type as an active learning strategy has an effect on students’ interest and response to social studies learning. From the questionnaire results, it was shown that the students’ interest and responses more increased after implementing the Card Sort type as an active learning strategy. The F-test hypothesis obtained a value of 48,9% or 0,489. This means that the effect of using the Card Sort type as an active learning strategy on students’ interest and response to social studies learning of 48,9% was classified as the big category.